2007
DOI: 10.1086/520827
|View full text |Cite
|
Sign up to set email alerts
|

MHD Simulations of Penumbra Fine Structure

Abstract: We present the results of numerical 3D magnetohydrodynamic ( MHD) simulations with radiative energy transfer of fine structure in a small sunspot of about 4 Mm width. The simulations show the development of filamentary structures and flow patterns that are, except for the lengths of the filaments, very similar to those observed. The filamentary structures consist of gaps with reduced field strength relative to their surroundings. Calculated synthetic images show dark cores like those seen in the observations; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
150
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 24 publications
21
150
0
Order By: Relevance
“…Petrie & Neukirch 1999) to studies of magnetoconvection (e.g. Heinemann et al 2007). A useful collection of these methods, and general sunspot physics, is presented in Thomas & Weiss (1992, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Petrie & Neukirch 1999) to studies of magnetoconvection (e.g. Heinemann et al 2007). A useful collection of these methods, and general sunspot physics, is presented in Thomas & Weiss (1992, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…3D MHD simulations of such structures (Nordlund 2006;Heinemann 2006) reproduce observed dark lanes running along the center of such structures (Lites et al 2004) and demonstrate that the origin of this dark structure is the same as proposed for the convective gap model. Of considerable importance is therefore that dark-cored light bridge structures occasionally show smooth transitions to dark-cored penumbral filaments (Langhans 2006;Scharmer et al 2007), strongly suggesting similar origin.…”
Section: Support From Observationsmentioning
confidence: 52%
“…Evidence for this conclusion comes from recent SOT/Hinode and SST observations Zakharov et al 2008), showing vertical flows of the right magnitude to explain the penumbral radiative heat flux. Recent numerical 3D MHD simulations (Heinemann et al 2007;Rempel et al 2008) reproduce fundamental properties of observed penumbrae and confirm the convective origin of penumbral filaments. The simulations show that the nature of this convection takes place in gaps with up to 2 Mm depth and that any roll-like convection (Danielson 1961;Rempel et al 2008), if present, is of small importance (Rempel et al 2008).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly pores, which are the smallest features clearly associated with the solar cycle have been studied and compared to observations [18] . More recently sunspots have been tackled, including sunspot umbrae and umbral dots [19] , light bridges [20] , and penumbral filaments [21,22] . Figure 5 is an image from the simulation by Rempel et al [22] , showing a sunspot umbra including umbral dots, a rudimentary penumbra as well as the quietSun.…”
Section: Activity: Flux Emergence Pores and Sunspotsmentioning
confidence: 99%